по алгебре 7 класс решебник ответы

Номер 692

 

Условие:

Докажите тождество:
а) (х - 3)(х + 7) - 13 = (х + 8)(х - 4) - 2;
б) 16 - (а + 3)(а + 2) = 4 - (6 + а)(а - 1).

 

Ответ:

a) (x - 3)(x + 7) - 13 = х2 + 7х - 3 - 21 - 13 = х2 + 4x - 34,
(x + 8)(x - 4) - 2 = х2 - 4х + 8х - 32 - 2 = х2 + 4x - 34 => (x - 3)(х + 7) - 13 = (x + 8)(x - 4) - 2;
б) 16 - (а + 3)(а + 2) = 16 - а2 - 2а - 3а - 6 = -а2 - 5а + 10,
4 - (6 + а)(а - 1) = 4 - 6а + б - а2 + а = -а2 - 5а + 10 => 16 - (а + 3)(а + 2) = 4 - (6 + а)(а - 1).

share with Whatsapp
share with Telegram
powered by social2s